The Effects of Vertically Propagating Tides on the Mean Dynamical Structure of the Lower Thermosphere. Issue 8 (17th August 2019) - Jones, McArthur; Forbes, Jeffrey M.; Sassi, Fabrizio
Abstract: Numerical experiments performed with the National Center for Atmospheric Research thermosphere‐ionosphere‐electrodynamics general circulation model forced with an observationally based diurnal and semidiurnal tidal spectrum are utilized to investigate the physical processes by which the dissipation of vertically propagating tides act to alter the zonally and diurnally averaged ("zonal‐mean") dynamical state of the thermosphere. Below 150 km the largest contributors to the zonal‐mean zonal wind distribution are the pressure gradient, Coriolis, and the tidally driven momentum flux divergence terms, the latter being about half the former two. Ion drag plays a smaller role in the lower thermosphere but becomes increasingly important at higher altitudes (i.e., above ∼150 km). We also find that the tidally driven heat flux divergence term contributes to the generation of zonal‐mean zonal winds through its coupling into the pressure gradient term. Tidally induced zonally and diurnally averaged zonal wind changes achieve values of up to 30 m/s in the lower thermosphere, of which about a third can be traced to the heat flux divergence. Tidal amplitudes used to force the thermosphere‐ionosphere‐electrodynamics general circulation model lower boundary represent conservative estimates, since they are based on forcing by a multiyear 60‐day mean tidal climatology, which significantly underestimates their amplitudes at any given time. Eliassen‐Palm Fluxes further support the conclusion that the heat flux divergence has a statistically significant direct impact on the zonal‐mean zonal wind balance in the lower thermosphere. Key Points: Heat flux divergences generated by dissipating tides impact the zonal and diurnal mean zonal winds in the lower thermosphere The major influence of the tidally driven heat flux divergence is to alter the pressure gradient force Tidal heat flux divergence alters the low‐ and middle‐latitude zonal and diurnal mean zonal winds by 20–40% depending on season in the TIE‐GCM